Challenges in the diagnosis of skin source basosquamous cell carcinoma: A case report - (:unkn) unknown (My University, 2013)
Bazal hücreli karsinom, çok sık görülen nadir metastaz ya- pan bir cilt kanseridir. Bazoskuamoz karsinom ise çok nadir görülen agresif seyreden ve sık metastaz yapan bazal hüc- reli karsinomun, histolojik alt tiplerinden biridir. Bu yazıda parotis bezinde kitle ile kliniğimize başvuran; ince iğne as- pirasyon biyopsisi sonucu pleomorfik adenom, patoloji so- nucu ise bazoskuamoz hücreli karsinom olarak rapor edilen 60 yaşındaki, hastaya klinik yaklaşımımızı ve literatürdeki yaklaşımları sunmaktayız.

One of the most common types of skin cancer is basal cell carcinoma, which is rarely seen to metastasise. Tis tumour has many histological subtypes, one of which is the rarely seen basosquamous carcinoma. Basosquamous carcinoma is considered an aggressive cancer with an in- creased risk of metastases. We report a 60 year-old patient who presented with a mass in his parotid gland as a result of fne-needle aspiration biopsy for pleomorphic ade- noma, who was diagnosed with basosquamous carcinoma.
Cilt kaynaklı bazoskuamoz hücreli karsinomun tanısında karşılaşılan zorluklar: Bir olgu sunumu
Keywords: Kulak, Burun, Boğaz